Association between parental unhealthy behaviors and offspring’s cardiovascular health status: Results from a cross-sectional analysis of parent–offspring pairs in China - Ma, Qi; Liu, Jieyu; Wu, Yu; Cui, Mengjie; Chen, Manman; Ma, Tao; Wang, Xinxin; Gao, Di; Li, Yanhui; Chen, Li; Ma, Ying; Zhang, Yi; et al. (Frontiers in Pediatrics, 2023)
Background: Cardiovascular health (CVH) in children and adolescents, which might be largely influenced by parental behaviors, may affect the incidence of cardiovascular diseases in adulthood. However, few studies have been conducted to explore the associations between parental behaviors and CVH status of offspring in China. Methods: Data were obtained from a cross-sectional survey conducted in Chinese children and adolescents aged 7-18 years old, with a total of 10043 parents-offspring pairs included. Parental behaviors included moderate to vigorous physical activity (MVPA), dietary behaviors, and weight status. The CVH status of offspring was consulted by The American Heart Association, including 7 factors. The associations between parental behaviors and CVH status of offspring were evaluated by multilevel logistic regression. Stratified analyses were conducted to explore the potential modifying influence of sociodemographic factors. Results: Most of the offspring had 5 ideal CVH factors, only 21.04% had 6-7 ideal CVH factors. Parental unhealthy behaviors were associated with high odds of non-ideal CVH status of offspring. Parental overweight / obesity, insufficient MVPA, and unhealthy dietary behaviors could increase the odds of owning 1-3 ideal CVH factors in offspring, with corresponding ORs (95% CI) of 1.61 (1.32 – 1.96), 1.31 (1.10 – 1.56), and 2.05 (1.43 – 2.94), respectively. There was a dose-response relationship between parental single unhealthy behavior and the odds of non-ideal CVH status in offspring (P-Trend <0.001). Offspring with overweight parents had ORs of 1.25 for non-ideal CVH status, compared to offspring with normal-weight parents. Among offspring who had the same number of ideal CVH factors, the cumulative association between unhealthy behaviors of parents and offspring’s non-ideal CVH status increased if parents had more unhealthy behaviors (P-Trend <0.001). Conclusions: Parental overweight/obesity, insufficient MVPA, and unhealthy dietary behaviors were strongly associated with CVH status in offspring. With a cumulative association, more unhealthy parental behaviors were associated with higher odds of offspring’s non-ideal CVH status, suggesting that targeting parental behaviors might facilitate attainment of improving CVH status of children and adolescents.